2022
DOI: 10.1007/s00404-022-06431-5
|View full text |Cite
|
Sign up to set email alerts
|

Second fertility-sparing surgery and fertility-outcomes in patients with recurrent borderline ovarian tumors

Abstract: Background At the time of recurrence, many borderline ovarian tumor (BOT) patients are still young with fertility needs. The purpose of this study is to evaluate the reproductive outcomes and recurrence rate of second fertility-sparing surgery (FSS) in women with recurrent BOTs. Methods Seventy-eight women of childbearing age diagnosed with recurrent BOTs from November 2009 to 2020 whose primary treatment was FSS were included. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Because recurrence may occur in patients with BOTs while they are still young and wishing to conceive someday, a second FSS may be performed after thorough consultation. Wang et al confirmed that a second FSS was as safe as radical surgery for recurrent BOTs with a pregnancy rate of 46.9% and a live birth rate of 81.3% [25]. In our study group, 8 of 71 patients with BOTs experienced tumor recurrence.…”
Section: Discussionsupporting
confidence: 72%
“…Because recurrence may occur in patients with BOTs while they are still young and wishing to conceive someday, a second FSS may be performed after thorough consultation. Wang et al confirmed that a second FSS was as safe as radical surgery for recurrent BOTs with a pregnancy rate of 46.9% and a live birth rate of 81.3% [25]. In our study group, 8 of 71 patients with BOTs experienced tumor recurrence.…”
Section: Discussionsupporting
confidence: 72%
“…This has also been observed in stage I sex cord stromal tumors [17] and, regardless of tumor stage, in BOT [18,19] and germ cell tumors [20]. Even a second fertility-sparing surgery could be considered safe in BOT after relapse following initial conservative surgery if pregnancy has not yet been achieved [21].…”
Section: Key Pointsmentioning
confidence: 86%
“…After a second fertility‐sparing procedure, 15 patients (32%) had a second recurrence. FIGO stage III is an independent prognostic factor for the second recurrence 12 …”
Section: Discussionmentioning
confidence: 99%
“…FIGO stage III is an independent prognostic factor for the second recurrence. 12 Patients desiring fertility-sparing procedures should be referred to an appropriate fertility specialist. The patient in this case wanted to become pregnant after the fourth surgery.…”
Section: Discussionmentioning
confidence: 99%